Structure and in vitro hypoglycemic activity of a homogenous polysaccharide purified from Sargassum pallidum. Issue 5 (3rd May 2019) - Cao, Changliang; Zhang, Bin; Li, Chao; Huang, Qiang; Fu, Xiong; Liu, Rui Hai
Abstract : A homogeneous polysaccharide (PSP-2) from Sargassum pallidum and its hypoglycemic activity. Abstract : This study aimed at investigating the structure, hypoglycemic activity and the underlying mechanism of a homogeneous polysaccharide (PSP-2) purified from Sargassum pallidum . Structural characterization revealed that PSP-2 with a molecular weight of 144.8 kDa was composed of fucose (21.6%), arabinose (2.5%), galactose (22.4%), glucose (2.2%), xylose (18.8%), mannose (1.2%), glucuronic acid (7.7%) and galacturonic acid (23.6%). The backbone chain of PSP-2 was composed of →1)-β-d -Xyl p -(3→, →1, 3)-β-l -Fuc p -(4→, →1)-α-d -Gal p -(6→, and →1)-α-d -Glc p NAc-(2→, and the side chains were composed of →1, 3, 6)-α-d -Gal p -(2→, →3)-β-l -Fuc p -(1, 4→, β-d -Gal p NAc-(1→, and α-d -Man p -(1→. In vitro hypoglycemic assays indicated that PSP-2 could significantly enhance glucose consumption, glycogen synthesis, and pyruvate kinase (PK) and hexokinase (HK) activities of insulin-resistant HepG2 cells. Furthermore, the underlying mechanistic studies revealed that PSP-2 could ameliorate insulin resistance by up-regulating the expression levels of insulin receptor substrate-1 (IRS-1), glycogen synthase (GS), phosphoinositide-3-kinase (PI3K) and glucose transporter-4 (GLUT4). These results suggested that PSP-2 may be a potential candidate for the prevention and treatment of Type 2 diabetes mellitus.